Vietnam Veterans Memorial Fund records - Vietnam Veterans Memorial Fund.
Administrative files consisting of correspondence, memoranda, telephone reports, minutes of meetings, speeches, writings, reports, notes, card files, legal and financial papers, blueprints and construction plans, illustrations, photographs, and other records documenting the administrative operations and technical resources required for the erection of the Vietnam Veterans Memorial as well as the surrounding political controversy. Includes material concerning the memorial designed by Maya Ying Lin, the sculpture by Frederick Hart, and the work of project director Robert Doubek, fund president Jan Scruggs, and individuals and companies involved in the design and building of the memorial including Binswanger Glasscraft Products, Larry Century, Cooper-Lecky Partnership, and Gilbane Building Company. Comments concerning the memorial include those of Tom Carhart, Milton R. Copulos, H. Ross Perot, Carlton Sherwood, and James H. Webb, Jr. Also includes transcripts from seminars held for the tenth anniversary commemoration which analyzed the effects of the Vietnamese conflict on the U.S. and correspondence and miscellaneous items relating to President Bill Clinton's participation in the 1993 Memorial Day ceremony.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
U.S. National Park Service.
Organization founded for the purpose of erecting a national memorial honoring American veterans of the Vietnam conflict.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carhart, Tom; Century, Larry; Clinton, Bill, -- 1946-; Copulos, Milton R; Doubek, Robert W; Hart, Frederick, -- 1943-; Lin, Maya Ying; Perot, H. Ross, -- 1930-; Scruggs, Jan C; Sherwood, Carlton; Webb, James H; Binswanger Glasscraft Products; Cooper-Lecky Partnership; Gilbane Building Company; Memorial Day; Vietnam Veterans Memorial (Washington, D.C.); Vietnam War, 1961-1975.; Vietnam War, 1961-1975 -- Monuments; Vietnam War, 1961-1975 -- Psychological aspects; War memorials -- Washington (D.C.)